Utilization of eggshell powder in one-part alkali-activated metakaolin based binder - Omur, Tarik; Miyan, Nausad; Kabay, Nihat (ELSEVIER SCI LTD, 2024)
Eggshell is a waste of poultry and the proper disposal of such waste products is a worldwide issue. Alkaline activation of calcium-rich eggshell powder (ESP) as a binder with a suitable aluminosilicate source offers the opportunity to produce viable materials. Thus, this paper reports the innovative use of ESP as a precursor in metakaolin (MK)-based one-part alkali-activated materials (AAMs). The impact of ESP on the fresh, physical, mechanical, and microstructural properties of one-part AAMs was studied. Upon the addition of ESP, the setting time was extended and a consistent reduction in semi-adiabatic heat release was observed. ESP favored the rheological characteristics of the mixtures by lowering viscosity and yield stress which enabled a decrease in the water content of ESP containing mortars. The incorporation of ESP up to 40 % improved the compressive strength by 22 % and 46 % for paste and mortar samples, respectively, and resulted in a notable mitigation of mortar shrinkage (only 300 mu epsilon at 56th days). ESP plays dual function in microstructure of AAM as a binder and micro-aggregate. C-A-S-H type gels were observed in ESP-rich mixes due to its calcium-rich structure, and the contribution of ESP on the hydration reactions were clarified in detail via X-Ray diffraction and thermogravimetric analysis. Life cycle analysis results indicated that incorporating ESP could obtain similar compressive strength while reducing the ecological impact.
Keywords: One-part alkali-activation; Eggshell waste; Metakaolin; Sustainability; Microstructure; Life cycle assessment; BLAST-FURNACE SLAG; CALCIUM-SILICATE-HYDRATE; DRYING SHRINKAGE; GEOPOLYMER; CEMENT; STRENGTH; CONCRETE; BEHAVIOR; RHEOLOGY; Construction & Building Technology; Engineering; Materials Science